Mineral trioxide aggregate or calcium hydroxide direct pulp capping: an analysis of the clinical treatment outcome - Mente, Johannes; Geletneky, Beate; Ohle, Marc; Koch, Martin Jean; Ding, Paul Georg Friedrich; Wolff, Diana; Dreyhaupt, Jens; Martin, Nicolas; Staehle, Hans Jörg; Pfefferle, Thorsten (Journal of endodontics, 2010)
Introduction - The use of mineral trioxide aggregate (MTA) might improve the prognosis of teeth after pulp exposure. The treatment outcome of teeth after direct pulp capping, either with mineral trioxide aggregate (MTA) or calcium hydroxide (controls), was investigated, taking into account possible confounding factors. - Methods - One hundred forty-nine patients treated between 2001 and 2006 who received direct pulp capping treatment in 167 teeth met the inclusion criteria. Treatment was performed by supervised undergraduate students (72%) and dentists (28%). Assessment of clinical and radiographic outcomes was performed by calibrated examiners 12-80 months after treatment (median, 27 months). - Results - One hundred eight patients (122 treated teeth) were available for follow-up (72.5% recall rate). A successful outcome was recorded for 78% of teeth (54 of 69) in the MTA group and for 60% of teeth (32 of 53) in the the calcium hydroxide group. The univariate analysis (generalized estimation equations model [GEE model] showed a significant difference in the success rate (odds ratio [OR], 2.36; 95% confidence interval [CI], 1.05-5.32; P = .04). In the multiple analysis (GEE model), the OR is marginally inside the nonsignificant range (OR, 0.43; 95% CI, 0.19-1.02; P = .05) when conspicuous confounding factors are stabilized (univariate analysis). Multiple analysis showed that teeth that were permanently restored ≥2 days after capping had a significantly worse prognosis in both groups (OR, 0.24; 95% CI, 0.09-0.66; P = .01). - Conclusions - MTA appears to be more effective than calcium hydroxide for maintaining long-term pulp vitality after direct pulp capping. The immediate and definitive restoration of teeth after direct pulp capping should always be aimed for.